PENGATURAN TENTANG TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL BERDASARKAN HUKUM POSITIF INDONESIA - Hafiz Sutrisno, Hafiz Sutrisno (Jurnal Inovasi Teknik Informatika, 2018)
Attack / Defamation is to say a word or set of words / sentences by alleging a certain act, and aimed at the honor and reputation of the person who may cause the person’s self-respect or dignity to be defamed, humiliated or demeaned. Social media is an online medium that supports social interaction and social media using web-based technology that transforms communication into interactive dialogue. The emergence of social media is very big influence for the community, both in terms of positive and negative, in terms of positive people can provide information without spending a large cost, whereas in the negative side can result in a criminal defamation case if in providing information that can harm someone’s good name. It is necessary to regulate criminal defamation through social media so that the self-esteem of the defiled person is not damaged, then the Law Number 11 Year 2008 on Electronic Information and Transaction has been established as the legal umbrella in anticipating the evil in the virtual world (cyber).